A resonant half-wave antenna for moisture content assessment in wood chips. (19th September 2019) - Merlan, Maria; Ditchi, Thierry; Oussar, Yacine; Holé, Stéphane; Géron, Emmanuel; Lucas, Jérôme
Abstract: The production of heat via combustion of wood biomass is growing because of the urge of European institutions to increase the use of renewable energies. Calorific value depends directly on the moisture content of the wood chips. Moisture content varies considerably from the rough conditions of the forest up to the wood industry chain. This paper presents a sensor based on a resonant half-wave antenna as a new approach for moisture determination of wood chips in piles. There is, at the moment, no system able to determine the global moisture content in a large sample of chips in a pile or in a truck. The sensor has to be placed into the material under test and the behavior of the antenna is analyzed to measure the moisture content. This method is tested on a one cubic meter scale setup in laboratory conditions. Promising results support the extended implementation to a real-scale production system.